Investing with Volume Analysis : Identify, Follow, and Profit from Trends - Dormeier, Buff (PH Professional Business, 2011)
In the continual pursuit for higher profits, investors and traders alike often assume significantly higher risks while chasing the next hot opportunity. Other more sophisticated investors attempt to employ complicated indicators while not fully understanding the information the indicator was designed to reveal. On the other hand, savvy investors employ analysis to gauge the market, positioning themselves to potentially earn higher profits with significantly less risk. Volume analysis attempts to delve deep inside the market trends to help identify shifts within the markets. Investing with Volume Analysis: Identify, Follow, and Profit from Trends presents an enlightened perspective on the role of volume, not only in pragmatic terms but also in terms of apprehending the underlying rationale of how and why. Award-winning technical analyst Buff Pelz Dormeier teaches state-of-the-art methods for analyzing the relationship of volume to price movements and the evolution of market trends.